2020
DOI: 10.2147/ibpc.s248579
|View full text |Cite
|
Sign up to set email alerts
|

<p>Renal Artery Stenosis in the Patient with Hypertension: Prevalence, Impact and Management</p>

Abstract: Atherosclerosis is the primary cause of renal artery stenosis. Atherosclerotic renal artery stenosis (ARAS) is associated with three clinical problems: renovascular hypertension, ischemic nephropathy and cardiac destabilization syndrome which pose huge healthcare implications. There is a significant rate of natural disease progression with worsening severity of renal artery stenosis when renal revascularization is not pursued in a timely manner. Selective subgroups of individuals with ARAS have had good outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 61 publications
0
15
0
2
Order By: Relevance
“…RAS not only results in hemodynamic disorders and deteriorating renal function, but is also exacerbated by systemic diseases including metabolic syndrome (MetS) and diabetes mellitus ( 3 ). Conversely, all of these risk factors are crucial contributors to atherosclerosis ( 4 ) and cardiovascular disease (CVD) ( 5 ), a leading cause of death in the U.S ( 6 , 7 ). Therefore, strategies to blunt kidney and cardiac damage in subjects with RVH with metabolic perturbation are in dire need.…”
Section: Introductionmentioning
confidence: 99%
“…RAS not only results in hemodynamic disorders and deteriorating renal function, but is also exacerbated by systemic diseases including metabolic syndrome (MetS) and diabetes mellitus ( 3 ). Conversely, all of these risk factors are crucial contributors to atherosclerosis ( 4 ) and cardiovascular disease (CVD) ( 5 ), a leading cause of death in the U.S ( 6 , 7 ). Therefore, strategies to blunt kidney and cardiac damage in subjects with RVH with metabolic perturbation are in dire need.…”
Section: Introductionmentioning
confidence: 99%
“…(4) In clinic, >½ moderate-to-severe RAS patients had bilateral lesions and both kidneys were related with prognosis [32] . However, patients included in our study had unilateral RAS [33] …”
Section: Limitationsmentioning
confidence: 89%
“…[ 32 ] However, patients included in our study had unilateral RAS. [ 33 ] (5) In addition, longer follow-up data are needed to evaluate the prognosis.…”
Section: Limitationsmentioning
confidence: 99%
“…In addition, for patients with severe stenosis requiring stenting, the degree of RAS was not significantly related to the risk of RFD ( 7 , 8 ). However, with the progress of contrast-enhanced ultrasound (CEUS) and other imaging omics, renal parenchymal blood perfusion was also an important factor ( 9 ). We have found that CEUS can evaluate renal parenchymal blood perfusion in real time, quantitatively and in a safe manner.…”
Section: Introductionmentioning
confidence: 99%